A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from northern Vietnam, southern China and central Laos - David, Patrick; Nguyen, Truong Quang; Nguyen, Tao Thien; Jiang, Ke; Chen, Tianbo; Teynié, Alexandre; Ziegler, Thomas (Zootaxa, 2012)
A new species of the genus Oligodon Fitzinger, 1826, Oligodon nagao sp. nov., is described on the basis of five specimensoriginating from Lang Son and Cao Bang provinces in northern Vietnam, Guangxi Autonomous Region in southernPeople’s Republic of China, and from Khammouane Province in central Laos PDR. This species differs from other speciesof the region by the combination of 15 or 17 dorsal scale rows at midbody, unforked hemipenes, not spinose but withpapillae, entire cloacal plate, a high number of ventrals, a rather short tail and dorsal pattern made of numerous dark,butterfly-shaped blotches. On the basis of the morphology of its hemipenes, Oligodon nagao sp. nov. belongs to the groupof Oligodon cinereus. This new species is compared with other species of the Indochinese Peninsula and China with 15or 17 dorsal scale rows, especially Oligodon joynsoni (Smith, 1917). An updated list of the Oligodon species of this region is provided.